A Study on Malaysian Medical Students’ Perception towards Career Opportunities and their Knowledge on Malaysia Health Care System - Kyaw Ko Latt; Muhammad Afif Ashraf Nor Ismadi; Nur Syahirah Md Radzi; Nur Elisya Aref; Naimah Nadiah Zainoodin; Aiena Dayini Hamsah; Nuraishah Emily Roslan (Asian Journal of Medicine & Health Sciences, 2022)
Introduction: Motivation is a psychological notion that is important in all aspects of a person’s life, including studies, education, and career choice. Lack of motivation in medical students’ life could be due to their lack of interest in medical education as well as to students’ worries and uncertainty about job security and job satisfaction in becoming a doctor. Most of the students who choose to pursue medical degree because of their own interest and their profound knowledge on recent health care system in Malaysia, but minority of them choose it because of their family influences and other reasons. Objective: To evaluate the knowledge and perception of medical students on Malaysia Health Care System and how much it has influence on their career opportunities after graduation. Method: This was a cross-sectional study, and 300 medical students from 27 medical universities/college across Malaysia participated in the study. Using convenience sampling method, online questionnaires were distributed through social media platforms and personal contact from 5 January to 13 January 2022. The questionnaires included the sociodemographic characteristics of medical students, their knowledge on Malaysia Health Care System and their attitude towards career opportunities after graduation. Statistical Package for Social Sciences (SPSS) was used to analysis the data and chi-square test was run to find out the associations among the study variables. Results: The study found that 73% of the respondents (n=219) had sufficient knowledge on Malaysia Health Care System and 76.7% of the respondents (n=230) had negative perception towards career opportunities after their graduation. Chi-square test showed that there was association between medical students’ knowledge on Malaysia Health Care System and the type of universities they were attending. Conclusion: Based on our finding, we can conclude that medical students with general knowledge on Malaysia Health Care System are more likely to understand their career pathways. However, some appropriate measures and initiatives should be taken by the policy makers, to improve views of Malaysia’s medical careers particularly among future medical graduates. More information on the current health care system and suitable psychological training for medical students who will become future medical officers in Malaysia’s health care system are two recommended measures that should be undertaken during medical students’ lifetimes.